Composition of Plankton in Water and Stomach Milkfish at Brackish Water Ponds - Arfiati, Diana (Proceedings of the International Conference on Green Technology; Vol 11 No 1 (2021): Proceeding of International Conference on Green Technology, 2021)
Abstract- Milkfish which cultivated in brackish water ponds utilize plankton as their natural feed. This study aimed to compare the abundance and type of phytoplankton, zooplankton in water and stomach milkfish also the water quality of brackish water ponds. This research uses survey method, samples were taken in 3 brackish water ponds. The composition of phytoplankton was found in three brackish water ponds with 4 divisions, in the fish stomach 6 divisions, zooplankton composition was founded 2 divisions and fish stomach 2 divisions. Milkfish consumed all composition of plankton in water. Based similarity index of plankton composition in water and stomach milkfish about 73%-80%. The water quality of the three brackish water ponds is classified as oligotrophic, abundance of phytoplankton in the range of 630 - 1122 cell/ ml and zooplankton 0-30 ind/ml. Water qualities are classified as good for milkfish cultivation. Therefore, it is recommended to keep the good condition of brackish water ponds.